PENGELOLAAN DANA DESA BEBAS FRAUD: PENDEKATAN EFEKTIF DI KECAMATAN TIDORE UTARA - Jeandry, Gregorius; Dara, Amin; Zainuddin, Zainuddin (Owner : Riset dan Jurnal Akuntansi, 2024)
Fraud occurs in several sectors, including the village sector, such as fraud in the management of village funds. Village funds that were initially to improve independent villages were not appropriately managed; the management of village funds is synonymous with abuse in management; this is evidenced by the statement "Village Fund Outlook 2018" issued by Indonesia Corruption Watch (ICW) in the village fund book published by the Ministry of Finance. As a result of ICW monitoring, in 2015–2017, cases of abuse in villages increased. In 2015, it reached 17 cases and increased to 41 cases in 2016. A more than twofold spike then occurred in 2017 with 96 cases. A total of 154 fraud cases, such as corruption and misuse of assets, were found. This study was conducted with the aim of examining the influence of village apparatus competence, internal control system, accountability, and morality on fraud prevention efforts in village fund management in North Tidore District, Tidore Islands City. The respondents used were 56 people consisting of village heads, village secretaries, heads of financial affairs, heads of planning affairs, staff of the head of planning affairs, heads of service sections, staff of the head of service sections, heads of government sections, staff of the head of government sections, technical implementers, heads of hamlets, heads of RWs and heads of RT. The data analysis technique used is multiple linear regression analysis. The results showed that the competence of village apparatus and internal control system has a positive and significant effect on fraud prevention. Conversely, morality and accountability have no impact on preventing fraud in village funds.